Generation and validation of a Leber Congenital Amaurosis, Type 12 patient-specific iPSC line (LVPEIi006-B) with a splice-site mutation in RD3 and an isogenic mutation-corrected iPSC line (LVPEIi006-B-1) - Sudipta Mahato; Savitri Maddileti; Trupti Agrawal; Sundaram Acharya; Chitra Kannabiran; Subhadra Jalali; Debojyoti Chakraborty; Indumathi Mariappan (Stem Cell Research)
Leber congenital amaurosis, Type 12 is an early onset, autosomal recessive retinal disease caused by mutations in RD3. We report the generation of a patient-specific iPSC line (LVPEIi006-B), using Sendai viral vector-based reprogramming approach and an isogenic, mutation-corrected iPSC line (LVPEIi006-B-1), using an en31FnCas9-based adenine base editor (ABE) system. Both lines were clonally expanded and genotyped to confirm the presence of patient-specific mutation and desired base correction in the edited line. Both lines maintained their stemness, pluripotency, genomic integrity and could differentiate into retinal organoids. The mutation-corrected, heterozygous iPSC-derived retinal organoids displayed a partial restoration of normal RD3 mRNA splicing.